Beginning JSP 2 - Haan, Peter den (Apress, 2012)
Welcome to Beginning JSP 2: From Novice to Professional. This book is for novices and teaches JavaServer Pages (JSP) 2 using basic principles. You don't need to know any Java to use this book because JSP 2 is a significant development of the JSP technology that has greatly reduced JSP's reliance on Java knowledge. However, to get the most out of supporting technologies and maximize your JSP applications, you need to know some basic Java techniques. We'll teach you these techniques and show you when and where to use the Java language.